ANALISIS ATAS PENERAPAN SISTEM PENGENDALIAN MANAJEMEN PEMBERIAN KREDIT PADA PT. SUZUKI FINANCE INDONESIA CABANG MANADO - Talumewo, Winda Emanuela; Nangoi, Grace; Tirayoh, Victorina (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Management control system is one way to achieve corporate / organizational goals with specific strategies effectively, efficiently, and economically. Implementation of a good management control system on crediting procedures to reduce the risks that may occur in credit sales activities, and is expected to ensure that the implementation of credit provision can be controlled. Goal to be achieved in this research is to know the procedure of giving credit at PT. Suzuki Finance Indonesia Manado branch and know the effectiveness of the implementation of management control system PT. Suzuki Finance Indonesia Branch Manado on lending. The object of this research is PT. Suzuki Finance Indonesia Branch Manado. The research method used is qualitative descriptive analysis method. The result of the research shows that credit procedure established by the company is clear and good and the implementation of the credit management control system has been running well and has been effective because it meets the elements of management control system.Keywords: Management Control System, Credit Procedure